2021
DOI: 10.1186/s40644-021-00407-5
|View full text |Cite
|
Sign up to set email alerts
|

Application of contrast-enhanced CT radiomics in prediction of early recurrence of locally advanced oesophageal squamous cell carcinoma after trimodal therapy

Abstract: Background Early recurrence of oesophageal squamous cell carcinoma (SCC) is defined as recurrence after surgery within 1 year, and appears as local recurrence, distant recurrence, and lymph node positive and disseminated recurrence. Contrast-enhanced computed tomography (CECT) is recommended for diagnosis of primary tumor and initial staging of oesophageal SCC, but it cannot be used to predict early recurrence. It is reported that radiomics can help predict preoperative stages of oesophageal SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Previous studies have shown that radiomics in computed tomography (CT) imaging can improve the prediction of prognosis of HNSCC . Radiomics on CT HNSCC imaging has been used to predict HPV status [8,9], overall survival [10][11][12][13][14], progression-free survival [10,[12][13][14], local tumour control [8,12,[15][16][17][18][19][20][21], tumour grade [9,22], lymph node response [23,24], tumour invasiveness [9,25], xerostomia [26][27][28], tumour resectability [29], and classifying molecular subtypes [30,31]. While the survival studies show that radiomics on CT data can significantly stratify patients in multiple survival groups, performance expressed through Harrell's C index ranged widely, from 0.58 to 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that radiomics in computed tomography (CT) imaging can improve the prediction of prognosis of HNSCC . Radiomics on CT HNSCC imaging has been used to predict HPV status [8,9], overall survival [10][11][12][13][14], progression-free survival [10,[12][13][14], local tumour control [8,12,[15][16][17][18][19][20][21], tumour grade [9,22], lymph node response [23,24], tumour invasiveness [9,25], xerostomia [26][27][28], tumour resectability [29], and classifying molecular subtypes [30,31]. While the survival studies show that radiomics on CT data can significantly stratify patients in multiple survival groups, performance expressed through Harrell's C index ranged widely, from 0.58 to 0.9.…”
Section: Introductionmentioning
confidence: 99%
“…Radiomics has also made progress in predicting the recurrence and prognosis of EC patients[ 44 - 47 ]. Tang et al [ 48 ] predicted the early recurrence of locally advanced ESCC after trimodal therapy based on enhanced CT radiomics. The results showed that in the training cohort, the AUCs of the radiomics model, the clinical model, and the combined model were 0.754, 0.679, and 0.821, respectively, and they were 0.646, 0.658, and 0.809 in the validation cohort; the combined model was the best.…”
Section: Radiomics Workflowmentioning
confidence: 99%
“…Based on existing preoperative examination methods, such as computed tomography, magnetic resonance imaging, and endoscopic ultrasonography, it is still difficult to accurately detect the presence of LNM. [12][13][14] In addition, the clinicopathological risk factors associated with LNM in SESC remain unclear. Therefore, this study aimed to determine the risk factors for LNM in patients with SESCC and establish a practical nomogram based on these factors to guide the treatment of patients with SESCC.…”
Section: Introductionmentioning
confidence: 99%